A new amphibious tetrapod from the Greenlandic Eotriassic - Bjerring, Hans C. (Meddelelser om Grønland. Geoscience, 1999)
The cranial anatomy, especially the allostotic parts, of a new tetrapod genus, Aquiloniferus, is described on the basis of four specimens from the Lower Triassic of central East Greenland at Kap Stosch. These specimens were studied briefly in the mid-1930s and assigned to four species of the trematosaur genus Lyrocephalus WIMAN. Herein it is suggested that only a single species, A. kochi, existed in this region, belonging to the Capitosauroidea.